Os periódicos acadêmicos de geografia francesa de 1940-1945. Entre a pobreza material e a resistência intelectual - Laurent Beauguitte (Confins)
Despite the war and the shortages it causes, despite the Occupation and both Vichy and German censorships, French geographers achieved, from 1940 to 1945, to continue their scientific work. This article aims to highlight both the production of French geographical journals during the World War II and the behaviour of geographers in this difficult time.If the impact of shortages can be easily quantified, it is also possible to find clear signs of resistance to the Occupation and the Vichy regime. Speaking of censorship as prisoners of war or the daily difficulties related to the Second World War, geographers evocated here clearly produce a contemporary geography.